Students Collaboration and Creative Mathematical Thinking Skills in Problem-Based Learning Using Numeracy Problems - Nora Nurhalita; Meryansumayeka Meryansumayeka; Scristia Scristia; Muhammad Yusup (Didaktik Matematika, 2024)
Collaboration and creative mathematical thinking are important for students. However, students' collaboration and creative mathematical thinking skills are still low because students are not used to collaborating or investigating the problem-solving process. This research aims to determine students' collaboration and creative mathematical thinking skills in the 10th grade in Problem-Based Learning using numeracy problems. This research was carried out on 25 vocational school students majoring in accounting in Palembang, Indonesia. The research method used was a mixed method. The results of research on students' collaboration skills show that most of the students are in the excellent category. Students can fulfill respect for others and commitment indicators, but the indicators of deliberation and participation are rarely fulfilled. The research results on students' creative mathematical thinking skills show that 80% are in the very good category, 16% are in the good category, and others are in the pretty good category. Students can fulfill three indicators, fluency, originality, and elaboration, but flexibility is rarely fulfilled. Creative thinking skills of students need to improve.